Reading the islamic city : discursive practices and legal judgment - Kahera, Akel Ismail, 1951- (Toposophia., 2012)
While it seems clear that the shari'ah had a formative influence on property rights, public space and land use, the primary aim of this book is to study what implications the practice of the Maliki school of Islamic law hav.